2018
DOI: 10.1016/j.firesaf.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Proceedings of the first workshop organized by the IAFSS Working Group on Measurement and Computation of Fire Phenomena (MaCFP)

Abstract: This paper provides a report of the discussions held at the first workshop on Measurement and Computation of Fire Phenomena (MaCFP) on June 10–11 2017. The first MaCFP work-shop was both a technical meeting for the gas phase subgroup and a planning meeting for the condensed phase subgroup. The gas phase subgroup reported on a first suite of experimental- computational comparisons corresponding to an initial list of target experiments. The initial list of target experiments identifies a series of benchmark conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The experiments considered here for validation purposes are all test cases of the MaCFP workshop [12] (https://iafss.org/macfp/) and were chosen by the authors since they have been identified by the fire community as the 'best' cases, at least to date, for CFD validation. A detailed description of the different test cases is already available (https://github.com/MaCFP), hence, only a brief overview is outlined here.…”
Section: Experimental Test Casesmentioning
confidence: 99%
“…The experiments considered here for validation purposes are all test cases of the MaCFP workshop [12] (https://iafss.org/macfp/) and were chosen by the authors since they have been identified by the fire community as the 'best' cases, at least to date, for CFD validation. A detailed description of the different test cases is already available (https://github.com/MaCFP), hence, only a brief overview is outlined here.…”
Section: Experimental Test Casesmentioning
confidence: 99%
“…The workshop served as a first technical meeting for the gas phase subgroup and a planning meeting for the condensed phase subgroup. The program of the workshop and copies of the presentations can be found at https://iafss.org/3770-2/; the proceedings that report on the content and main outcomes of the workshop were published in Fire Safety Journal [1].…”
Section: First Macfp Workhop (June 2017)mentioning
confidence: 99%
“…An example of a public database of material properties is found in the Validation Guide of the Fire Dynamics Simulator (FDS) 5 . Currently, an international effort is underway to further develop experimental and modeling tools such as these in order to “advance predictive fire modelling” 6 . The present manuscript presents work based on a coordinated effort to develop a comprehensive database of material properties for use in fire models.…”
Section: Introductionmentioning
confidence: 99%
“…5 Currently, an international effort is underway to further develop experimental and modeling tools such as these in order to "advance predictive fire modelling". 6 The present manuscript presents work based on a coordinated effort to develop a comprehensive database of material properties for use in fire models. This database will include both raw data from a suite of milligram-scale tests and a list of properties for each material that could be directly used as inputs for a fire model such as FDS.…”
Section: Introductionmentioning
confidence: 99%